PENGARUH KECERDASAN INTELEKTUAL, MINAT BELAJAR DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Suryaningtyas, Oksa (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
The research carried out was to determine the extent of the influence of intellectual intelligence, interest in learning, learning behavior on the level of understanding of accounting. The research was conducted on accounting students at a high school of economics in the city of Semarang by determining the sample using purposive random sampling where the research sample was determined to be 100 respondents. From the results of data processing from the SPSS program it was found that all research variables of intellectual intelligence, interest in learning and learning behavior had a positive effect and significant for understanding accounting where the biggest influencing variable is intellectual intelligence with a value of 0.298.